USAGE OF NEUROMARKER (S100 PROTEIN) AND FLOW CYTOMETRY FOR COMPARATIVE ASSESSMENT OF NMDA-RECEPTOR ANTAGONISTS' EFFECT ON NEUROPROLIFERATIVE PROCESSES IN RETINA AND OPTIC NERVE IN CASE OF MODELLED OPHTHALMIC ISCHEMIA-REPERFUSION - Chereshnyuk, I.L.; Povkh, V.L.; Zagorii, G.V.; Khodakovskyi, A.A.; Ostra, E.A. (World of Medicine and Biology, 2016)
The purpose of the study is to investigate the changes of the proliferative processes cells in retina and optic nerve during postreperfusional period of acute ocular ischemia using the flow cytometric analysis and measurement of neuromarker activity, and to assess the efficacy of NMDA receptor antagonists in case of mentioned pathology. Such investigation aims not only the implementation of the new methods for pre-clinical research of drugs with neurotropic vector of pharmacological activity, but allows assessment of the possibility for already known drugs used in neurological practice to be applied for the new indication, particularly as neuroretinoprotectors. In the course of research we determined the significant increase of percentage ratio of the cells in DNA synthetic phase (phase S) to their total amount in the tissue suspension for a median of 7,46 times in the modelled 60 minute ophthalmic ischemia-reperfusion at the end of the first day of observation. This is followed by the increase of neuroglial proliferation marker (S100 protein) titer for a median of 32,6 times (7th day). Comparative assessment of the NMDA receptor antagonists' effect on neuroproliferative processes in retina and optic nerve in case of modelled ophthalmic ischemia-reperfusion using the change of S100 protein titer as neuromarker, together with the flow cytometry method, showed that the most significant effect on the mentioned processes was expressed by ademol. The data of enzymatic test show that this drug has significant advantage of memantine and magnesium sulfate solution, and correlates with the last mentioned by the cytological index of proliferative activity (intensification of S-phase of cell cycle). Іt is reasonable and rational to use the proposed methods and markers for the assessment of the value and grade of ischemic injury retina and optic nerve, and the investigation of NMDA receptor antagonists is prospective for clinical assessment using the new indication - as neuroretinoprotectors.
Keywords: ademol; memantine; magnesium sulfate; NMDA receptor antagonists; neuroretinoprotection